First all-flavor search for transient neutrino emission using 3-years of IceCube DeepCore data. Issue 1 (18th January 2022) - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J.A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves , A.A.; Amin, N.M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al.
Abstract: Since the discovery of a flux of high-energy astrophysical neutrinos, searches for their origins have focused primarily at TeV-PeV energies. Compared to sub-TeV searches, high-energy searches benefit from an increase in the neutrino cross section, improved angular resolution on the neutrino direction, and a reduced background from atmospheric neutrinos and muons. However, the focus on high energy does not preclude the existence of sub-TeV neutrino emission where IceCube retains sensitivity. Here we present the first all-flavor search from IceCube for transient emission of low-energy neutrinos, focusing on the energy region of 5.6-100 GeV using three years of data obtained with the IceCube-DeepCore detector. We find no evidence of transient neutrino emission in the data, thus leading to a constraint on the volumetric rate of astrophysical transient sources in the range of ∼ 705-2301 Gpc -3 yr -1 for sources following a subphotospheric energy spectrum with a mean energy of 100 GeV and a bolometric energy of 10 52 erg.